2019
DOI: 10.1108/lhtn-06-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Usability testing for a community college library website

Abstract: Purpose This paper details a usability testing case study on a simplified homepage for [Library]. The usability testing was completed in Spring 2017 to meet the needs of diverse user groups and shifting trends in Web design and development. At the conclusion of the usability testing, recommendations for change informed the design decisions and a new homepage was implemented in October 2018. Design/methodology/approach The researcher performed eight usability tests with a combination of the different library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
0
15
0
5
Order By: Relevance
“…Chong and Law (2018) carried out a rigorous literature review on airline website evaluation studies and found that the websites of airlines need major rework. Valenti (2018) carried out usability testing of a community college library website and found major issues on the website, which need to be fixed to make usage of users more convenient. Danielson et al (2014) have carried out a usability testing of an HIV prevention website in Africa and found that users feel website helpful but there is need to fix some usability aspects such as navigation design.…”
Section: Related Workmentioning
confidence: 99%
“…Chong and Law (2018) carried out a rigorous literature review on airline website evaluation studies and found that the websites of airlines need major rework. Valenti (2018) carried out usability testing of a community college library website and found major issues on the website, which need to be fixed to make usage of users more convenient. Danielson et al (2014) have carried out a usability testing of an HIV prevention website in Africa and found that users feel website helpful but there is need to fix some usability aspects such as navigation design.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, the use of websites has impacted information sharing and communication among business owners and their customers (Devi and Verma, 2018; Okechukwu and Anunobi, 2020 ). In the libraries, websites are used as an important gateway to various information resources and services such as access to scholarly databases, online public access catalogue, research tools and useful links for research and academic purposes ( Arshad and Ameen, 2015 ; Dominguez et al, 2015 ; Devi and Verma, 2016; Gohain, 2019 ; Valenti, 2019 ). The library websites are used to give general information such as library history, facilities, working hours, staff and contact information ( Herring, 2007 ; Sife and Tandika, 2014 ; Gohain, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the library websites represent their respective libraries at the local and international level ( Okechukwu and Anunobi, 2020 ). Therefore, effective management of the library websites is essential to facilitate its accessibility, ease of navigation and information discovery as well as communication between libraries and their users ( Valenti, 2019 ). This paper intends to present how websites of the universities and research libraries in Tanzania had responded to the outbreak of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…De maneira geral, observa-se no mercado brasileiro que os testes de usabilidade moderados costumam levar de 30 minutos a 1 hora de duração. Conforme mencionado, é bastante comum e uma boa prática entregar algum tipo de recompensa ao usuário no final da avaliação, como uma forma de agradecimento pela sua participação e tempo dedicado ao teste (VALENTI, 2018;VANDECREEK, 2005).…”
Section: Escala De Usabilidade Do Sistema -"System Usability Scale" (...unclassified
“…Medir tempo de tarefa é uma importante métrica de usabilidade, pois permite acompanhar de forma simples até que ponto a velocidade e a eficiência da experiência se apresentam para os usuários (VALENTI, 2018;MADRIGAL-CADAVID, 2020). Isso pode significar o quanto os usuários estão entendendo a tela ou fluxo, se a carga mental é grande ou não para executar a tarefa, se as informações estão claras etc.…”
Section: Medindo O Tempo Na Realização Da Tarefaunclassified